MEDIA KOMUNIKASI PILIHAN KARYAWAN DALAM ALIRAN PESAN DARI ATASAN KE BAWAHAN (DOWNWARD COMMUNICATION) - Ariani AA, Prida (Scriptura, 2008)
In an organization, to ensure the succeed of an organizational communi-cation, we need to have a good communication between superiors and sub-ordinates (downward communication), but very often there are mixed communi¬cation in the lower level due to the incomplete information by the time a message reached the lower level employee. The usage of proper downward communication tools can help to minimize the downward filtering and mixed message. The communication tools that are used to send message from the upper level to lower level, whether it’s oral or written are considered important additional facility for downward communication. This research is using qualitative approach with focus group discussion method. The research result indicates that in every type of downward communication which consist of task instruction, rational, ideology, information and feedback, the employees are using different downward communi¬cation tools with different reason or different encouragement factor of tools usage too.